2015
DOI: 10.1093/geront/gnv027
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Research on the Arts, Aging, and Quality of Life

Abstract: There is a need for programs of research (instead of teams conducting only one study), the development and application of conceptual frameworks, and multiple perspectives in order to build knowledge about how the arts contribute to health and QoL for older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 14 publications
2
49
0
3
Order By: Relevance
“…These elements are perhaps more related to the 'intrinsic' value of drama: its unique qualities and the enjoyment it provides. Whilst these findings resonate with the now substantive body of literature that shows that involvement in the arts in all its forms has multiple benefits for the health and well-being of individuals and society (Fraser et al, 2015), more research is needed to understand and capture the specific merits of drama, as well as the potential impact they may have on other aspects of older people's lives. In addition, the longer term health and wellbeing outcomes are underexplored, if at all, underlining the unsatisfactory quality of much research design in this area.…”
Section: Health and Well-beingmentioning
confidence: 59%
See 1 more Smart Citation
“…These elements are perhaps more related to the 'intrinsic' value of drama: its unique qualities and the enjoyment it provides. Whilst these findings resonate with the now substantive body of literature that shows that involvement in the arts in all its forms has multiple benefits for the health and well-being of individuals and society (Fraser et al, 2015), more research is needed to understand and capture the specific merits of drama, as well as the potential impact they may have on other aspects of older people's lives. In addition, the longer term health and wellbeing outcomes are underexplored, if at all, underlining the unsatisfactory quality of much research design in this area.…”
Section: Health and Well-beingmentioning
confidence: 59%
“…Indeed, the UK's Arts and Humanities Research Council (AHRC) carried out an evidence review in 2014 on 'the value of the arts and culture to people and society' which refers to the challenge of the impact of an ageing population on public services and asserts the value of the arts in promoting older people's physical, mental and social well-being, particularly concentrating on the benefits of dance. However, by only focusing on well-being, the AHRC review presents a somewhat reductionist assessment of the potential cultural value of older people's participation in arts activities: an observation reinforced by a recent scoping review in this very journal looking at research on the arts, ageing and quality of life (Fraser et al, 2015).…”
mentioning
confidence: 99%
“…The fact of being involved on a variety of activities (cultural/artistic, intellectual, social) is important in old age, due to its impact on different dimensions of life. For example, in a review that analyzed qualitative, quantitative, and mixed methods, including different artistic activities such as music and painting, it was found that artistic engagement could contribute to health and quality of life in older adults 47. In the same way, it has been reported that active participation in arts such as dance, expressive writing, music (singing and instrumental), theater arts, and visual arts has been related to mental and physical improvements in memory, creativity, problem solving, everyday competence, reaction time, balance/gait, and quality of life 48…”
Section: Resultsmentioning
confidence: 99%
“…The combination of hoping and coping may increase subjective well‐being through what George (2010) called discrepancy theory—the belief that a person’s subjective well‐being will be highest when there is low discrepancy between one’s aspirations and achievements. There is evidence that quality of life is enhanced by the ability to cope, whether through attitudinal or social strategies, or the use of artistic expression (Fraser et al, 2015). In fact, emotional wellness was found to be more positively associated with cognitive health than physical, social, spiritual, or intellectual wellness (Strout & Howard, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%